CALCULATION OF FEES FOR MAKING APPLICATION ENVELOPE IN CV. ABC USING MICROSOFT EXCEL XP 2002 - Novi Astutyningsih; Rosadi Aqwam Kardian, Skom.,MM. (Jurnal Sistem Informasi, 2003)
Writing contains about problems that arise in the system to calculate the cost ofmaking the envelope on the CV. ABC. Authors megusulkan an application thatcontains the envelope in order to calculate the manufacturing process becomes muchfaster calculation.